The Nature and Characteristics of Domestic Sports Tourism in Central Africa: The Case of Cameroon - Siyabulela Nyikana; Tembi. M. Tichaawa (African Journal of Hospitality, Tourism and Leisure, 2022)
This study is premised on the idea that sporting events have been used as part of strategic tourism development, particularly for the domestic tourism market. The study examines the nature and characteristics of domestic sport tourism in Central Africa using the context of Cameroon. Using data collected from event attendees (n=963) across multiple events within various time frames, and interviews conducted with 16 key stakeholders involved in sport and tourism, the key findings from this enquiry revealed that many of the domestic sport tourists are educated and employed youth, who travel to different provinces from urban cities and are motivated by both the sport and VFR intentions. They tended to link the event attendance with other commitments with friends and relatives as well as trading and business endeavours in the informal business sector. Thus, the study contributes to an enhanced understanding of domestic sports tourism, especially within the Central African region underscoring its significance as a sector with potential to further harness domestic tourism benefits for host destinations.